CCBE1 mutation causing sclerosing cholangitis: Expanding the spectrum of lymphedema‐cholestasis syndrome. Issue 1 (9th May 2017) - Viveiros, André; Reiterer, Marion; Schaefer, Benedikt; Finkenstedt, Armin; Schneeberger, Stefan; Schwaighofer, Hubert; Moser, Patrizia; Sprenger, Rudolf; Glodny, Bernhard; Vogel, Wolfgang; Janecke, Andreas R.; Zoller, Heinz
Abstract : A 52‐year old patient presented with lymphedema, protein loosing enteropathy, and sclerosing cholangitis and was diagnosed with lymphedema cholestasis syndrome (LCS). Cholangioscopy revealed dilated lymphatic vessels obstructing the bile duct and compound heterozygosity for collagen and calcium‐binding epidermal growth factor domain‐containing protein 1 ( CCBE1 ) mutations was identified defining a novel type of LCS. (Hepatology 2017;66:286–288).